Budget goal clarity as a mediator in the relationship between budgeting practices and budgetary performance in healthcare (European journal of volunteering and community-based projects, 2025)
Purpose - This paper draws on the Behavioral Management Accounting (BMA) literature and applies Goal-setting theory to propose a research model that examines how the cognitive effects of a specific budgeting practice - budgetary participation - influence budget goal clarity, which in turn affects budgetary performance in a healthcare setting. Furthermore, the model explores how the relationship between budgetary participation and performance is mediated by an underexplored individual-level variable: budget goal clarity. Budget goal clarity is recognized as particularly important in contexts where budget holders are not traditional managers but hybrid professionals - responsible for both clinical and financial outcomes - who often have limited familiarity with managerial tools and financial target goals, a circumstance that could influence their attitudes, behaviors and performance.Design/approach - The study administered a cross-sectional survey to a sample of medical doctors working in a public hospital who were identified as budget holders.Findings - The findings reveal that: (i) budgetary participation has a direct effect on budget goal clarity; (ii) budget goal clarity subsequently impacts budgetary performance; and (iii) budget goal clarity mediates the relationship between budgetary participation and budgetary performanceOriginality/value - This paper contributes to the existing BMA literature on hybrid settings by suggesting that incorporating budget goal clarity as a mediator in the budgetary participation–performance relationship offers a novel perspective on the cognitive and perceptual dynamics shaping the psychological mechanisms that link the positive cognitive effects of participatory budgeting to attitudes, behaviors and, ultimately, to budgetary performance.